Tribological Behavior of Hydraulic Cylinder Coaxial Sealing Systems Made from PTFE and PTFE Compounds - Deaconescu, Andrea; Deaconescu, Tudor (MDPI, 2020)
Current trends concerning hydraulic cylinder sealing systems are aimed at decreasing energy consumption which can be materialized by minimizing leaks and reducing friction. The latest developments in the field of materials and sealing system geometries as well as modern simulation possibilities allow maximum performance levels of hydraulic cylinders. Reducing friction is possible by hydro-dynamic separation of the sliding and sealing points already at very low velocities and by using materials, such as plastomers, from polytetrafluoroethylene (PTFE) (virgin PTFE and filled PTFE). It is within this context that this paper discusses a theoretical and experimental study focused on the tribological behavior of coaxial sealing systems mounted on the pistons of hydraulic cylinders. It presents a methodology for the theoretical determination of the lubricant film thickness between the cylinder piston and the seal. The experimental installation used for measuring fluid film thickness is presented, and the results obtained under various working conditions are compared to the theoretical ones. For the analyzed working conditions related to pressure, speed, and temperature, the paper concludes with a set of criteria for the selection of the optimum seal material so as to maximize energy efficiency.
Keywords: coaxial sealing systems; hydrodynamic friction; pressure distribution; virgin PTFE; filled PTFE